Remember Hard But Think Softly: Metaphorical Effects of Hardness/Softness on Cognitive Functions - Xie, Jiushu; Lu, Zhi; Wang, Ruiming; Cai, Zhenguang G. (Frontiers in Psychology, 2016)
Previous studies have found that bodily stimulation, such as hardness, biases social judgment and evaluation via metaphorical association; however, it remains unclear whether bodily stimulation also affects cognitive functions, such as memory and creativity. The current study used metaphorical associations between “hard” and “rigid” and between “soft” and “flexible” in Chinese, to investigate whether the experience of hardness affected cognitive functions requiring either rigidity (memory) or flexibility (creativity). In Experiment 1, we found that Chinese-speaking participants performed better at recalling previously memorized words while sitting on a hard-surface stool (the hard condition) than a cushioned one (the soft condition). In Experiment 2, participants sitting on a cushioned stool outperformed those sitting on a hard-surface stool on a Chinese riddle task, which required creative/flexible thinking, but not on an analogical reasoning task, which required both rigid and flexible thinking. The results suggest the hardness experience affects cognitive functions that are metaphorically associated with rigidity and flexibility. They support the embodiment proposition that cognitive functions and representations could be grounded via metaphorical association in bodily states.